Elucidating phylogenetic relationships and genus‐level classification within the fungal family Trypetheliaceae (Ascomycota: Dothideomycetes). Issue 5 (1st October 2014) - Nelsen, Matthew P.; Lücking, Robert; Aptroot, André; Andrew, Carrie J.; Cáceres, Marcela; Plata, Eimy Rivas; Gueidan, Cécile; da Silva Canêz, Luciana; Knight, Allison; Ludwig, Lars R.; Mercado-Díaz, Joel A.; Parnmen, Sittiporn; et al.
Abstract: While the phylogenetic position of Trypetheliaceae has been the subject of recent molecular studies, the relationships within this family have been little studied. Here we construct a detailed genus‐level phylogeny of the family. We confirm previous morphology‐based findings suggesting that a substantial proportion of genera are not monophyletic, and that an overemphasis has been placed on certain character state combinations which do not strictly reflect phylogenetic relationships. Specifically, patterns of ascospore septation, ostiole orientation and type of ascomatal aggregation are evolutionarily labile, and of limited utility for the delimitation of genera as currently circumscribed. We show that species from a number of genera including Astrothelium, Bathelium, Cryptothelium, Laurera and Trypethelium together form a strongly supported group, referred to here as the "Astrothelium" clade. Species from Aptrootia, Architrypethelium, Campylothelium, Marcelaria ( L. purpurina and L. cumingii groups ), Pseudopyrenula and species from the Trypethelium eluteriae group fall outside of the " Astrothelium " clade and each form monophyletic groups. In contrast, species from Arthopyrenia, Mycomicrothelia and Polymeridium fall outside of the " Astrothelium " clade, and do not form monophyletic groups. The data presented here validate earlier morphology‐based findings suggesting generic delimitations are in need of revision, and provides a first step towards identifying the utility of individual characters and identifying which characters and character state combinations may be useful for future classification.